Effects of Concentration and Temperature on Corrosion and Scale Inhibitive Behavior of Uncaria gambir Extract for Low-Carbon Steel in Cooling-Water Solution - Jiraphan Pleanteangthume (2021)
© 2020, Allerton Press, Inc. Abstract: The corrosion inhibition property of the Uncaria gambir extract (UGE) for the low-carbon steel was investigated in a prepared cooling-water solution using gravimetric analysis and potentiodynamic polarization measurements. Anticorrosive effectiveness was tested at the UGE concentrations of 0–1500 ppm and temperatures of 40–60°C. The CaCO3 scale inhibition performance was evaluated following NACE standard TM 0374-2007 and ASTM D511-03. The surface morphology was analyzed by scanning electron microscopy. It was found that increasing the UGE concentration increased its anticorrosive effectiveness. A 70% corrosion inhibition efficiency and a 31% CaCO3 scale inhibition efficiency were observed during the use of 1500 ppm UGE. A change in the morphology of CaCO3 precipitate was observed due to the adsorption of the UGE, which suppressed the regular growth process. Increasing temperature decreased the effectiveness of the UGE. A higher corrosion potential and a reduction of anodic reactivity were also observed. The UGE acted as anodic inhibitor and conformed the Langmuir adsorption isotherm.